2015
DOI: 10.1186/s13058-015-0657-1
|View full text |Cite
|
Sign up to set email alerts
|

“New” metastases are associated with a poorer prognosis than growth of pre-existing metastases in patients with metastatic breast cancer treated with chemotherapy

Abstract: IntroductionProgression-free survival (PFS) and overall survival (OS) endpoints often only weakly correlate. This analysis investigates how different progression events impact on OS, using data from two phase 3 studies with eribulin in women with advanced/metastatic breast cancer (MBC).MethodsIn Study 301, 1102 women with ≤2 prior chemotherapies for advanced/MBC were randomized to eribulin mesylate (1.4 mg/m2 on days 1 and 8 every 21 days) or capecitabine (1.25 g/m2 twice daily on days 1–14 every 21 days). Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…One potential surrogate endpoint is the development of metastases at new sites [30, 31]. It is hypothesized that a successful anti-CSC treatment will impact on the time to developing new metastases and on the proportion of patients progressing with new metastases rather than on the progression of pre-existing metastases which is likely due to non-BCSC, bulk tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…One potential surrogate endpoint is the development of metastases at new sites [30, 31]. It is hypothesized that a successful anti-CSC treatment will impact on the time to developing new metastases and on the proportion of patients progressing with new metastases rather than on the progression of pre-existing metastases which is likely due to non-BCSC, bulk tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been used in earlier studies in other cancers [4,5]. We believe that this is the best approach in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…One earlier study of breast cancer suggested that a new endpoint, defined as the time from randomization to progression with new metastasis or death, might improve the predictivity on OS [4]. It has been noted that it can be difficult to identify progression and measure lesions accurately by assessing pre-existing lesions, especially when the baseline lesions are small [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations